EFFECTS OF PRE-GERMINATION TREATMENTS AND STORAGE ON GERMINATION OF Astronium fraxinifolium SCHOTT (ANACARDIACEAE) DIASPORES - Lílian de Lima Braga; Priscyla Maria Silva Rodrigues; Yule Roberta Ferreira Nunes; Maria das Dores Magalhães Veloso (Ciência Florestal, 2014)
The goal of this study was to evaluate the germination and the storage capacity of Astronium fraxinifolium diaspores. Six pre-germination treatments were used in the experiment: control treatment (intact diaspores); diaspores immersed in water at room temperature (25º C) for 5 min; diaspores immersed in water at 70° C for 5 min; diaspores immersed in water at 100° C for 5 min; diaspores immersed in sodium hypochlorite solution (1:1000) for 2 min; and diaspores mechanically scarified with sandpaper #80. To evaluate storage conditions, we tested two different types of packaging (permeable paper bag and transparent glass jar) and two environmental conditions (cold chamber and room conditions), resulting in four treatments. The germination tests were performed for zero (control) and 60, 120, 180, 240, 300 and 360 days after storage. The effects of different treatments on germination and storage of diaspores were evaluated by ANOVA, followed by Tukey test. Regarding to pre-germination treatments, high germination rates were observed in the hypochlorite (98.0 ± 4.22%), control (97.0 ± 4.83%), water at room temperature (96.0 ± 6.99%) and water at 70º C (83.0 ± 29.08%) treatments. Thus, Astronium fraxinifolium diaspores do not present dormancy. During storage, the diaspores remained viable throughout the study period with high germination rates, except for the treatment in paper bags placed in the cold chamber, in which the diaspores lost their viability in the eighth month of storage. Therefore, this is not a recommended storage method for this species.